Development of Absorbed Blasting Vibration Energy Index for the Evaluation of Human Comfort in Multistorey Buildings. (31st May 2017) - Yao, Qiang; Yang, Xingguo; Li, Hongtao
Abstract : There have been civil disputes and complaints regarding the negative effects of blasting vibration on buildings around the blasting site. By considering the effect of blasting vibration on a human body as a process of energy transfer and conversion, the human body absorbed blasting vibration energy (ABVE) index has been developed for comfort evaluation. Using dynamic monitoring and theoretical analysis, the elevation amplification effect and selective amplification effect on different frequency components of the ABVE have been investigated. The elevation amplification factor and selective amplification coefficients on different frequency components of the ABVE index for a typical 4-storey brick and concrete building have been determined. Based on the results, the magnitude and frequency components of the ABVE index in different parts especially in different storeys for the typical building have been determined. According to the characteristics of human body's response to vibrations of different frequencies, the frequency-based weighting method of ABVE index has been simplified. By calculating the combined effect of vibrations from all directions, the total human body ABVE and its frequency components at different floors of the building can be determined accurately. This can be used to evaluate the human body comfort against blasting vibration at different floors.